2020
DOI: 10.1007/s40487-020-00130-4
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Controversies in Management and Surveillance of Early-Stage Melanoma

Abstract: The incidence of cutaneous melanoma continues to rise dramatically worldwide, presenting a significant burden to the healthcare system. Despite this, there is still controversy in the guidelines regarding follow-up surveillance for patients with thin melanoma. Since there are no randomized clinical trials to support evidence-based guidelines for follow-up surveillance, dermatologic and oncologic organizations have developed their own recommendations based on expert opinion. However, these recommendations diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The conventional approach also has its disadvantages—it can burden patients with too-frequent visits that negatively affect the medical benefit for the patient—especially in the era of the COVID-19 pandemic, which poses a risk of cross-infection [ 6 , 7 , 8 , 9 ]. Increasing the frequency of visits may also have a negative impact on hospital facilities, as it increases the cost of medical care, which globally has limited resources both in economic terms and in terms of manpower [ 10 ]. Another disadvantage for the patient is over-imaging, which increases the risk of exposure to radiation and overtreating [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conventional approach also has its disadvantages—it can burden patients with too-frequent visits that negatively affect the medical benefit for the patient—especially in the era of the COVID-19 pandemic, which poses a risk of cross-infection [ 6 , 7 , 8 , 9 ]. Increasing the frequency of visits may also have a negative impact on hospital facilities, as it increases the cost of medical care, which globally has limited resources both in economic terms and in terms of manpower [ 10 ]. Another disadvantage for the patient is over-imaging, which increases the risk of exposure to radiation and overtreating [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the frequency of visits may also have a negative impact on hospital facilities, as it increases the cost of medical care, which globally has limited resources both in economic terms and in terms of manpower [ 10 ]. Another disadvantage for the patient is over-imaging, which increases the risk of exposure to radiation and overtreating [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Marushchak et al suggested that the high cost of screening and potentially increased rates of lesion excisions, as well as overimaging and overtreating, pose serious concerns [31]. The integration of RCM in the diagnostic patient pathway improves diagnostic power for melanoma detection through the addition of morphologic clues, thereby reducing unnecessary excisions compared to dermoscopy [20].…”
Section: Discussionmentioning
confidence: 99%
“…Only roughly 10%-20% of melanoma patients will be diagnosed with subsequent melanoma, whereby the risk of subsequent melanoma is highest within the first 3 years after initial melanoma diagnosis [5]. Notwithstanding this evidence, most guidelines and dermatologists advocate lifelong surveillance with at least annual visits for all melanoma, irrespective of tumor thickness, effective risk of recurrence/progression or presence of additional risk factors [6,7]. Addressing the problem of melanoma over-diagnosis in this light, which refers to early melanomas that will never cause symptoms or death during a person expected lifetime, the uncritical overtake of this practice results in long term over-surveillance of a significantly increasing cohort of virtually "cured" healthy individuals.…”
Section: Timely Detection and Prompt Treatment Have Been Declaredmentioning
confidence: 99%